First Report of Molecular Characterization of Extended Spectrum Beta-Lactamase-Producing Acinetobacter baumannii among Debilitated Patients in Tertiary Care Hospital, Ebonyi State, Nigeria: Extended Spectrum β-Lactamase-Producing A. Baumannii - Egwu, Ikechukwu Herbert; Egwu-Ikechukwu, Modesta Mmaduabuchi; Oke, Boniface; Nnabugwu, Charity Chinyere (Iranian Journal of Pharmaceutical Sciences, 2024)
Extended Spectrum Beta Lactamase (ESBL)-Producing Acinetobacter baumannii has threatened patients’ optimal healthcare in various tertiary care hospitals globally. The paucity of information regarding this life-threatening organism in Nigeria necessitated this research. Hence, this study aimed to molecularly characterize ESBL-producing A. baumannii among debilitated patients in a tertiary care hospital in Ebonyi State, Nigeria. Debilitated patients admitted in the intensive care unit (ICU), medical, surgical, and orthopedic wards were sampled, and 385 clinical samples were obtained from them over a six-month study period. Standard microbiological methods were used to identify A. baumannii isolates, while 16S rRNA PCR was used to confirm the isolates molecularly. The Kirby-Bauer disc diffusion techniques were used to ascertain the antibiotic sensitivity profiles of A. baumannii isolates. The double disc synergy test (DDST) method was employed to determine ESBLs production among the isolates, while to determine A. baumannii isolates harboring blaTEM, blaSHV, and blaOXA genes, PCR techniques were used. A total of 23 (6%) A. baumannii isolates were recovered from 385 clinical samples. The isolated A. baumannii exhibited multidrug resistance (MDR) traits, while 43.5% of the isolates were ESBL-producing A. baumannii. Also, 9 (90%) and 3 (30%) of the isolated A. baumannii harbored blaTEM and blaOXA genes, respectively, while no isolate harbored the blaSHV gene. The isolated A. baumannii were observed to harbor ESBL genes. Importantly, this is the first report of ESBL-producing A. baumannii in Ebonyi State, Nigeria.